Learning Model at SD Muhammadiyah 3 Pandaan During the Covid-19 Pandemic - Harnum Putri Almaidah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to describe the learning implementation model during the COVID-19 pandemic at SD Muhammadiyah 3 Pandaan. The research was conducted at SD Muhammadiyah 3 Pandaan City with one of the teachers as resource persons. This research uses descriptive qualitative research. The results of this study are observations of learning models at SD Muhammadiyah 3 Pandaan during the covid-19 pandemic. Learning that is usually carried out in person is now being shifted to distance learning or daring. In the implementation of learning during this pandemic, appropriate and effective learning models are needed to support the success of the teaching and learning process. The application of the learning model is one of the main factors in the learning process. This is because when applying the appropriate learning model, the learning process and learning outcomes will be as expected. There are several factors that support teachers in the learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to the factors that support bold learning, there are also several inhibiting factors for teachers in bold learning. The inhibiting factors include not all students have cellphones and there are still many parents who are busy working.